Queensland Telepaediatric Service: A Review of the First 15 Years of Service - Smith, Anthony C.; Armfield, Nigel R.; Coulthard, Mark G.; Williams, Michael L.; Caffery, Liam J. (Frontiers in Digital Health, 2020)
In November 2000, the Queensland Telepaediatric Service (QTS) was established in Brisbane, Australia, to support the delivery of telehealth services to patients and clinicians in regional and remote locations. The QTS was built on a centralised coordination model, where telehealth services could be effectively managed by a dedicated telehealth coordinator. In doing so, telehealth referral and consultation processes were efficient and clinicians felt better supported as they adjusted to new processes for engaging with patients. We have conducted a retrospective review of activity associated with the QTS and summarised key activities which have arisen from this extensive program of work. Telehealth service records and associated publications were used to describe the evolution of the QTS over a 15-year period. From November 2000 to March 2016, 23,054 telehealth consultations were delivered for 37 paediatric clinical specialties. The most common service areas included child and youth mental health, neurology, burns care, surgery, and ear nose and throat services. A range of different telehealth service models were developed to align with different clinical service needs and location of services. Whilst most work involved video consultation between hospitals, some services involved the delivery of telehealth services into the home, schools or community health centres. Despite its longevity, the QTS was not immune to the usual challenges associated with telehealth implementation, service redesign and sustainability. Experience reported from the QTS will be useful for other health services seeking to develop comprehensive telehealth services in a rapidly changing healthcare environment.